2021
DOI: 10.3390/app11125689
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Actin Filament Quantification and Cell Shape Modeling of Osteoblasts on Charged Ti Surfaces

Abstract: Surface charges at the cell–biomaterial interface are known to determine cellular functions. Previous findings on cell signaling indicate that osteoblastic cells favor certain moderately positive surface charges, whereas highly positive charges are not tolerated. In this study, we aimed to gain deeper insights into the influence exerted by surface charges on the actin cytoskeleton and the cell shape. We analyzed surfaces with a negative, moderately positive, and highly positive zeta (ζ) potential: titanium (Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…This suggests that amino-rich surfaces possess high cell adhesion capacity. The slow cell migration is also the effect of the moderately positive surface charges from the amine groups on the surfaces, and this is supported by the works of Gruening et al [57], who showed that moderately positive surface charges exhibit a higher number of long actin filaments that promote cell-material adhesion. The changes in the cells' circularity over time also correlate with the cell spreading and gene expression results.…”
Section: Discussionmentioning
confidence: 80%
“…This suggests that amino-rich surfaces possess high cell adhesion capacity. The slow cell migration is also the effect of the moderately positive surface charges from the amine groups on the surfaces, and this is supported by the works of Gruening et al [57], who showed that moderately positive surface charges exhibit a higher number of long actin filaments that promote cell-material adhesion. The changes in the cells' circularity over time also correlate with the cell spreading and gene expression results.…”
Section: Discussionmentioning
confidence: 80%
“…In signal receiving cells co-cultured with signal sending cells, Notch activation increases with the area of contact between the two cell types 40 . To directly test whether synNotch output in vivo correlates with the contact area between synNotch and ligand cells, we developed a vertex-based 41,42 mathematical model with mechanochemical coupling between cell-cell contact length and synNotch output (see Fig. 1(D) and Materials and Methods Sections 2-4 for details).…”
Section: Resultsmentioning
confidence: 99%
“…1(C i,ii)). To address this, we developed a novel vertex-based 36,37 mathematical model with mechanochemical coupling between vertex dynamics and intracellular synNotch output (see Fig. 1(D) and Materials and Methods Sections 2-4 for details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter, electrotaxis, also termed galvanotaxis, is being increasingly studied, in particular in keratinocytes and fibroblasts, since it may provide a promising strategy to foster skin wound healing ( Liang et al, 2020 ), ( Cho et al, 2018 ), ( Lin et al, 2017 ), ( Saltukoglu et al, 2015 ). Electric fields are an attractive approach for manipulating cell behavior because of their broad application across multiple cells and tissue types ( Dawson et al, 2020 ; Gruening et al, 2021 ). In most cells, the direction of migration seems to be cathodal (e.g., in fibroblasts and mesenchymal stem and corneal epithelial cells ( Lin et al, 2017 ) ( Zhao et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%